Toward Sustainable Islamic Banking: The Role of FinTech, Knowledge Management, Green Banking, and Sharia Compliance - Nurcahyo, Satria Avianda; Ferdianto, Raditya; Arismaya, Anisa Dewi; Anis, Muhammad (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2025)
Islamic banking is facing increasing pressure to adopt sustainable business practices while maintaining compliance with sharia principles. In this context, Financial Technology (Fintech), Knowledge Management, Green Banking, and Sharia Compliance have emerged as critical factors influencing sustainability. This research aims to examine sustainable business models in Islamic banking in Central Java by analyzing the interrelations among these factors. A quantitative approach using Structural Equation Modeling Partial Least Squares (SEM-PLS) was applied to data from 515 sharia bank employees. The findings indicate that Fintech significantly influences Green Banking, Knowledge Management, and business sustainability, but does not directly affect Sharia Compliance. Green Banking significantly impacts both Sharia Compliance and business sustainability, while Sharia Compliance mediates the relationship between Green Banking and sustainability. These results highlight the need for deeper integration between Fintech and Islamic principles. Islamic banks are encouraged to develop strategies that synergize technological innovation, environmental responsibility, and religious compliance to achieve long-term, sustainable growth.